Diversity of causal fungi in weed diseases and potential use as a biological weed control for vegetable plots in Thailand - Duangporn Suwanagul; Anawat Suwanagul (Journal of Current Science and Technology, 2013)
The study was aimed to isolate and identify the causal microorganism of leaf spot and blight disease of weeds. Seven species of weeds showing leaf spot and leaf blight diseases were collected from vegetable-producing areas in Central Thailand. These were Cyperus rotundus (Cyperaceae), Cyperus brevifolius (Cyperaceae), Brachiaria mutica (Poaceae), Eleusine indica (Poaceae), Dactyloctenium aegyptium (Poaceae), Pennisetum polystachyon (Poaceae), and Oryza sativa f. spontanea (Poaceae). The causal microorganisms were isolated from leaf symptoms by tissue transplanting and moist chamber techniques. Identification was based on their morphological features and examined under stereo and light binocular microscopes. From this study, a total of 25 isolates of causal fungi comprised of 10 genera with 15 species identified, were found. These were Alternaria alternata, Bipolaris bicolor, Colletotrichum capsici, Colletotrichum gloeosporioides, Colletotrichum graminicola, Colletotrichum musae, Curvularia lunata, Curvularia pallescens, Drechslera holmii, Fusarium oxysporum, Fusarium semitectum, Fusarium solani, Myrothecium cinctum, Nigrospora oryzae, Pestalotiopsis guepinii, Phomopsis sp. A pathogenicity test of D. holmii inoculums consisting of spore suspensions of 1x106 spores/ml of D. holmii, were performed onto healthy weeds, D. aegyptium and Brassica alboglaba. It was shown that only D. holmii caused severe damage on their weed hosts, whereas disease symptom occurred on B. alboglaba. This can be concluded that specificity of D. holmii on D. aegyptium showed great potential utilization of fungus as a biological control agent for weed control in B. alboglaba vegetable plots.